2014
DOI: 10.1002/app.40481
|View full text |Cite
|
Sign up to set email alerts
|

Improving the thermal and mechanical properties of poly(vinyl butyral) through the incorporation of acid‐treated single‐walled carbon nanotubes

Abstract: In this study, to investigate the effect of functionalized carbon nanotubes on the thermal and mechanical properties of the poly(vinyl butyral) (PVB) resin, PVB/functionalized single-walled carbon nanotube (f-SWCNT) composites were fabricated by a solution casting method. The functionalized nanotubes were prepared by acid treatment. The formation of oxygen-containing functional groups on the surface of the nanotubes was confirmed by Fourier transform infrared spectroscopy, energy-dispersive X-ray spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
(33 reference statements)
3
13
0
Order By: Relevance
“…In other words, at about 1 wt% SWCNT content, the critical point was reached and lower improvement compared to the virgin PVC film was observed. This behavior was reported in many studies . In this sample, the tensile strength was increased only 9.6% and the Young's modulus was reduced 4% relative to the neat PVC.…”
Section: Resultssupporting
confidence: 86%
“…In other words, at about 1 wt% SWCNT content, the critical point was reached and lower improvement compared to the virgin PVC film was observed. This behavior was reported in many studies . In this sample, the tensile strength was increased only 9.6% and the Young's modulus was reduced 4% relative to the neat PVC.…”
Section: Resultssupporting
confidence: 86%
“…The SEM image for the PVC/SWCNT showed that the carbon nanotubes generated bridges in cracks and, consequently, improved the mechanical and thermal properties of the composite. This has been reported in our previous works . These bridges could act as an obstacle for plasticizer migration.…”
Section: Resultssupporting
confidence: 79%
“…These composites may also have repeated structural units of size less than 100 nm . Polymer nanocomposites have drawn great attention of many researchers because of their improved properties by the addition of nanoparticles in the polymer matrix . Polymer composites with nanoparticles have more advantages over composites with microparticles because they improve the thermomechanical properties without any reduction in dielectric strength and improve the degradation stability .…”
Section: Introductionmentioning
confidence: 99%